Imatinib radiosensitizes bladder cancer by targeting homologous recombination. - Qiao, B; Kerr, M; Groselj, B; Teo, M; Knowles, M; Bristow, R; Phillips, R; Kiltie, A (2013)
Radiotherapy is a major treatment modality used to treat muscle-invasive bladder cancer, with patient outcomes similar to surgery. However, radioresistance is a significant factor in treatment failure. Cell-free extracts of muscle-invasive bladder tumors are defective in nonhomologous end-joining (NHEJ), and this phenotype may be used clinically by combining radiotherapy with a radiosensitizing drug that targets homologous recombination, thereby sparing normal tissues with intact NHEJ. The response of the homologous recombination protein RAD51 to radiation is inhibited by the small-molecule tyrosine kinase inhibitor imatinib. Stable RT112 bladder cancer Ku knockdown (Ku80KD) cells were generated using short hairpin RNA technology to mimic the invasive tumor phenotype and also RAD51 knockdown (RAD51KD) cells to show imatinib's pathway selectivity. Ku80KD, RAD51KD, nonsilencing vector control, and parental RT112 cells were treated with radiation in combination with either imatinib or lapatinib, which inhibits NHEJ and cell survival assessed by clonogenic assay. Drug doses were chosen at approximately IC40 and IC10 (nontoxic) levels. Imatinib radiosensitized Ku80KD cells to a greater extent than RAD51KD or RT112 cells. In contrast, lapatinib radiosensitized RAD51KD and RT112 cells but not Ku80KD cells. Taken together, our findings suggest a new application for imatinib in concurrent use with radiotherapy to treat muscle-invasive bladder cancer. Cancer Res; 73(5); 1611-20. ©2012 AACR.